PENYIDIKAN TINDAK PIDANA KEHUTANAN DALAM BENTUK TIDAK DILENGKAPI SECARA BERSAMA SURAT KETERANGAN SAHNYA HASIL HUTAN - Okyusran, Daslucky (UNES Journal of Swara Justisia, 2018)
Forestry criminal acts in the form of not being accompanied together with a certificate of legality of forest products are prohibited acts as mentioned in Article 83 paragraph (1) letter b of Law Number 18 Year 2013 concerning Prevention and Eradication of Forest Destruction. The provision is used as a legal basis for investigators to ensnare the perpetrators of forestry crime, because it not only violates the law but is also a violation of the socio-economic rights of the community so that in an effort to combat criminal acts in the forestry sector, investigation as part of law enforcement must carried out effectively by conducting a mechanism of investigation properly and applying the elements of the article violated appropriately against the crime as done by the Special Criminal Investigation Directorate of the West Sumatra Regional Police.